Modelica-based heating surface modelling and dynamic exergy analysis of 300 MW power plant boiler - Guo, MengMeng; Hao, Yongsheng; Nižetić, Sandro; Lee, Kwang Y.; Sun, Li (Energy conversion and management, 2024)
•A dynamic model for a 300 MW subcritical power plant boiler is developed.•A novel dynamic exergy analysis and assessment model is proposed.•The influence of drum level control on dynamic exergy behavior is evaluate.•The asynchronous responses are discussed in flow and heat transfer processes.•The dynamic exergy analysis reveals exergy destruction rates of heating surfaces. In the era of high penetration of renewable energy sources (RESs), traditional coal-fired power plants are facing increasing requirements of operational flexibility which is limited by the inherent slow dynamics of boiler. To this end, this paper presents a comprehensive dynamic model of the heating surfaces for a 300 MW power plant boiler and analyzes the exergy performance from the perspective of transient responses. Based on the object-oriented modelling language Modelica, the multi-domain first-principal model is developed by unifying the equations of thermal, mechanical, liquid and control components and interfaces. The model accuracy is validated by the field measurements. The model takes into account the multi-scale time constants in terms of the flow and heat transfer processes and drum level control. As an extension to the conventional steady-state thermodynamic analysis, a methodology of dynamic exergy analysis and evaluation is proposed. Dynamic simulation results well describe the initial reverse response of the drum level, i.e., false water level indicator, as a result of which the mass flow rate of feedwater exhibits the oscillatory performance. It is revealed that the step disturbances of flue gas mass flow and feedwater temperature, respectively, renders the temperature responses in different positions being of multi-scale setting-time and magnitudes. The exergy evaluation reveals that the water-wall suffers from the largest dynamic exergy destruction, approximately 8.2 and 8.5 times higher than the superheater and economizer, respectively. Economizer is the most sensitive component to the drum level control performance, whose dynamic exergy performance oscillates significantly. The proposed dynamic modelling and analysis method in this paper lays a solid foundation for the development of dynamic optimal control in power plants.